A candidate fusion engineering material, WC-FeCr. (October 2018) - Humphry-Baker, Samuel A.; Harrison, Robert W.; Greaves, Graeme; Knowles, Alexander J.; Smith, George D.W.; Donnelly, Stephen E.; Lee, William E.
Abstract: A new candidate fusion engineering material, WC-FeCr, has been irradiated with He ions at 25 and 500 °C. Ions were injected at 6 keV to a dose of 15 dpa and 50 at. % He, simulating direct helium injection from the plasma. The microstructural evolution was continuously characterised in situ using transmission electron microscopy. In the FeCr phase, a coarse array of 3–6 nm bubbles formed. In the WC, bubbles were less prominent and smaller ( 2 nm). Spherical-cap bubbles formed at hetero-phase interfaces of tertiary precipitates, indicating that enhanced processing routes to minimise precipitation could further improve irradiation tolerance. Graphical abstract: Unlabelled Image